PHYSICAL ACTIVITY OF ELEMENTARY SCHOOL STUDENTS IN URBAN AREAS POST COVID-19 PANDEMIC - Nugroho, Agung Wahyu; Wibowo, Moch. Septian Resi; Kurniawan, Arif; Mulyadi, Rekyan Woro Mulaksito; Listyarini, Anastasia Erlina; Supriyanto, Agus; Iswanto, Ari (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2025)
The peri-urban area is an area located on the outskirts, so that students' physical activity can still be found in various places. However, the current view is different after the Covid-19 pandemic, currently students tend to do very minimal physical activity. In addition to the loss of interest in doing physical activity due to the closure of all public facilities, the impact of gadget addiction for elementary school students affects the management of students' emotional processing. This study aims to (1) examine the physical activity of elementary school students in the peri-urban area, (2) determine the physical activity of students after Covid-19 in the peri-urban area, and (3) reveal the factors that influence the physical activity of students in the peri-urban area. This study is descriptive quantitative. The population used in public elementary schools in the suburbs was 169 students. The sampling technique for this study was taken using the simple random sampling technique. The physical activity measurement instrument in this study used the Physical Activity Questionnaire–Children (PAQ-C). Data analysis used descriptive statistics expressed in the form of percentages. The results of the study showed that the physical activity of students in the peri-urban area showed that 82 students (48.52%) had good activity conditions. Meanwhile, as many as 87 students (51.47%) had poor physical activity conditions. This provides a real picture that the Covid pandemic that occurred can reduce the physical activity conditions of elementary school students. Then the physical activities that are widely carried out by students in peri-urban areas include football, walking, cycling, jogging, futsal and other physical activities. Students' physical activity after the pandemic is influenced by the Covid disaster management policy with social restrictions, changes in sedentary lifestyles during online learning activities, technological advances that cause students to prefer games that use less physical activity and the lifestyle of students' parents. The conclusion of this study is that the Covid-19 pandemic has an effect on students' physical activity which is correlated with the health conditions of students in peri-urban areas.